2021
DOI: 10.3390/ijms22094575
|View full text |Cite
|
Sign up to set email alerts
|

NUP-98 Rearrangements Led to the Identification of Candidate Biomarkers for Primary Induction Failure in Pediatric Acute Myeloid Leukemia

Abstract: Conventional chemotherapy for acute myeloid leukemia regimens generally encompass an intensive induction phase, in order to achieve a morphological remission in terms of bone marrow blasts (<5%). The majority of cases are classified as Primary Induction Response (PIR); unfortunately, 15% of children do not achieve remission and are defined Primary Induction Failure (PIF). This study aims to characterize the gene expression profile of PIF in children with Acute Myeloid Leukemia (AML), in order to detect mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Results reported here advance our knowledge on the biology and biochemistry of SPINK2, one member of the SPINK family of protease inhibitor, and shed new light on the physiological and pathophysiological meaning of its temporary enzymatic inhibition. Our work I) shows the physiological expression of SPINK2 in adult human bone marrow HSPCs and in peripherally mobilized CD34 + cells and provides a confirmation of its expression in a wide range of malignant hematological cancers, 11 , 12 , 13 , 43 , 44 II) defines, by in vitro experiments, the kinetic properties of trypsin inhibition by SPINK2 and SPINK2 degradation by trypsin and introduces them in mathematical relationships able to model long progress curve (TI-model), III) includes a thorough analysis of serine proteases gene expression in HSPCs of human adult bone marrow and shows for the first time the presence of PRSS2 (trypsin-2 or anionic trypsin) and PRSS57 (NSP4) in bone marrow HSPCs and mobilized CD34 + hematopoietic cells, and IV) provides a quantitative theoretical background (TI-D theory) to the possible physiological meaning of the temporary enzyme inhibition properties of SPINKs.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Results reported here advance our knowledge on the biology and biochemistry of SPINK2, one member of the SPINK family of protease inhibitor, and shed new light on the physiological and pathophysiological meaning of its temporary enzymatic inhibition. Our work I) shows the physiological expression of SPINK2 in adult human bone marrow HSPCs and in peripherally mobilized CD34 + cells and provides a confirmation of its expression in a wide range of malignant hematological cancers, 11 , 12 , 13 , 43 , 44 II) defines, by in vitro experiments, the kinetic properties of trypsin inhibition by SPINK2 and SPINK2 degradation by trypsin and introduces them in mathematical relationships able to model long progress curve (TI-model), III) includes a thorough analysis of serine proteases gene expression in HSPCs of human adult bone marrow and shows for the first time the presence of PRSS2 (trypsin-2 or anionic trypsin) and PRSS57 (NSP4) in bone marrow HSPCs and mobilized CD34 + hematopoietic cells, and IV) provides a quantitative theoretical background (TI-D theory) to the possible physiological meaning of the temporary enzyme inhibition properties of SPINKs.…”
Section: Discussionsupporting
confidence: 57%
“…Our group has recently reported that SPINK2 is overexpressed in a subset of pediatric acute myeloid leukemias (AMLs) and such overexpression is associated with a form of primary chemoresistance to the standard treatment for this form of leukemia. 11 Indeed, upregulation of SPINK2 has been previously observed in adult AML patients, and its expression has been reported as an indicator of poor prognosis. 12 Moreover, it has been reported that SPINK2 is significantly elevated in several leukemia cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…When fused to the N-terminus of NUP98, the NSD1-SET gains transforming activities in hematopoietic cells, resulting in myelodysplasia and AML, and the presence of a NUP98-NSD1 (and other NUP98-fusions) is often associated with primary resistance to chemotherapy [ 86 , 87 ]. Functional studies suggested that transformation by these fusions involves the NUP98-GFLG repeats recruiting a large WDR82-SET1A/B-COMPASS protein complex to promote H3K4 trimethylation and favor active transcription [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SPINK2 is closely related to the development of cancer, and high levels of SPINK2 transcripts can be detected in patients with primary skin follicular center cell lymphoma (102). Upregulation of SPINK2 gene expression in patients with acute myeloid leukemia is associated with poor prognosis (103,104). SPINK2 is significantly elevated in most of the leukemia cell lines studied and plays an important role in tumor progression and response to treatment (97).…”
Section: Spink2 Indicates Poor Tumor Prognosis and Inhibits The Progr...mentioning
confidence: 99%